The Use of Puppet Drama to Engage Speaking Skills of Young Learners - Wulan, Retno; Pratiwi, Agnes Iga; Manar, Marsandi (Universitas Batanghari Jambi, 2025)
Young learners’ engagement is crucial to construct their identity and sense of belonging both within and outside the classrooms. This study aimed at investigating how the integration of puppets and drama enhanced young learners’ engagement in learning English and increasing their speaking performance. Employing a classroom action research, 22 students of the fifth and sixth grade of an English extracurricular program of one private primary school in Jambi Province, Indonesia, were involved. The researchers conducted two cycles for total four months from the observation to the reflection stages. Both cycles consisting of total five meetings defined how effective the use of puppets and drama in enhancing these young learners’ speaking ability. The current study revealed that the integration of puppets and drama contributed to increasing student’s engagement and enhancing their speaking performance. The findings have implication for students’ high participation, better self-confidence in speaking performance, and greater sense of affinity within their classroom.